Secrecy Analysis of Directional mmWave UAV-Based Links Under Hovering Fluctuations - Saud Althunibat (16888722) (2023)
Recent developments in Unmanned Aerial Vehicles (UAVs) technology have paved the way to their utilization in different fields and applications. Among these applications, UAVs have been widely investigated as a good candidate to serve as mobile base-stations that can provide prompt and temporary coverage of wireless connectivity for specific areas. Recent studies that address different UAVs’ performance aspect lack of considering more practical channel models. Therefore, in this paper, based on a recent three dimensional channel modeling of UAV-based links, the secrecy analysis is in detail conducted for UAV-based links operating on the millimeter wave band. Specifically, the average channel capacity, the average secrecy capacity and the probability of strictly positive secrecy capacity are all investigated between two UAVs in the presence of another UAV-based eavesdropper. Our results include closed form expressions of the addressed secrecy metrics along with simulation results that reveal the impact of different operational parameters on the secrecy performance. Other Information Published in: IEEE Open Journal of the Communications Society License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/ojcoms.2023.3316919